Pelaksanaan Perlindungan Hukum Mitra Penerima Waralaba Atas Risiko Kerugian Yang Ditimbulkan Oleh Pemberi Kemitraan - Gosal, Grace Anna Belle; Urbanisasi, Urbanisasi (Jurnal Ilmiah Wahana Pendidikan, 2023)
Franchising is an agreement regarding the distribution method of goods and services to consumers, in which the business is operated according to the procedures and methods set by the franchisor, and the franchisor provides assistance to the franchisee. The author's research addresses the issue of legal protection for franchises regarding the risks of losses caused by the franchisor's mistakes. The research method used is juridical-normative, which involves examining the relevant legislation related to the underlying issues raised. The research findings indicate that the implementation of legal protection for franchises regarding the risks of losses caused by the franchisor's mistakes shows that the franchise agreement serves as the applicable legal foundation in operating the agreed-upon relationship. This agreement provides both preventive and punitive legal protection. However, there are obstacles and efforts to protect the franchisee, as the assumption that the franchisee is prohibited from transferring the received know-how to others may be less appropriate, as Article 3 of the Ministry of Trade Regulation allows for the inclusion of provisions for subsequent franchise agreements.